Kemampuan Literasi Matematika Siswa Sekolah Dasar Indonesia - Ari Indriani; Dwi Erna Novianti (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2018)
This study aimed to know the mathematical literation skill of elementary student. This study was qualitative descriptive approach. This study was held in SD Negeri 3 Kunduran. The population of this study was 5th grade with 39 students. The sampling was used saturation sampling technique. The data was collected using obervation, essay test, and documentation. Before the essay test was used, it was analyzed its content validity, level of difficulty, discrimination power, and reliability. Test was consist of 4 questions. The data technique was qualitative analysis with Miles and Hubermen model. This research showed that students who can worked on level 4 question were students who answered more correctly on question number 2. Students who can worked on level 3 question were students who answer more correctly on question number 4.This study concluded that the mathematical literation skill of 5th grade student in SD Negeri 3 Kunduran was good.